Impact of silver nanoparticles as antibacterial agent derived from leaf and callus of Celastrus paniculatus Willd - Anita Solanki; Dipika Rathod; Illa C. Patel; Jitendriya Panigrahi (SpringerOpen, 2021)
Abstract Background Celastrus paniculatus Willd. is a rich source of numerous active constituents such as celapanigin, celapagin, malkangunin, celapanin, zeylasteral, pristimerin, and zeylasterone which render medicinal properties to its various parts. Therefore, the present work provides a protocol for the synthesis of AgNPs from in vivo leaf and in vitro developed callus extract of C. paniculatus and both the extracts have great antibacterial potential, which may give immense support for the drug preparation using AgNPs prepared from this valuable medicinal plant. Results High frequencies of calli induced from leaves and its counterpart, i.e., the natural part leaf were selected as the experimental materials for the green synthesis. The collected data exhibited gradual color variations started with whitish color, creamish, and after 8 weeks it ultimately turns into a solid mass of brownish callus. The silver nanoparticles (AgNPs) were synthesized using in vivo fresh leaves and in vitro developed callus extracts with an indication of brown colored complex. Further confirmation of AgNPs synthesis in both the samples was done using UV-visible spectral analysis followed by X-ray diffraction (XRD) analysis, Fourier transformation infrared spectroscopy (FTIR), and scanning electron microscopic (SEM) analysis. Conclusion The antibacterial activity of both extracts reflected the presence of the zone of inhibition in both gram-positive and gram-negative bacteria. AgNPs derived from callus extract showed better results with 24.00 ± 1.00 mm zones of inhibition. This protocol deserves the recognition of the antibacterial potential of AgNPs synthesized from CP plant extracts.